Hubungan antara Komunikasi Verbal Orang Tua dengan Prestasi Belajar Siswa di SMK Dwija Praja Pekalongan - Nunung Hasanah (Pena Medika Jurnal Kesehatan, 2010)
Family has culture to communicates with child by well could create good pre condition for its grow of children intelligence. Comunication was looked at as process to change person behaviour. Study performance was result that got in the form impressions that cause of individual itself as result from activity in study. The objective of the research was to know correlation between verbal communication of parent with study performance of student. The research type was quantitative with cross sectional approach and carried out by using research instrument in the form of questionnaire. Independent variable in the research was varbal communication of person while the dependent variable was study performance of student. Sample in this research was student of 2nd class and 3nd class as much as 100 students at SMK Dwija Praja Pekalongan. From result of statistics test by using chi square test and a = 0,005 got result that there is correlation between verbal communication of parent with study performance of student at SMK Dwija Pekalongan (p value = 0,000). From result of the research shows there is correlation between verbal communication of parent with study performance of student at SMK Dwija Praja Pekalongan.Keywords : verbal communication, study performance, correlation